A Directional Control Auxiliary Thrust System to Increase the Forward Speed of a Quadcopter UAV - Chanapan Srijun; Nattawoot Depaiwa (Engineering and Technology Horizons, 2024)
This research introduces a method to increase the horizontal speed of a quadcopter UAV using an auxiliary thrust system that can be adjusted in direction. The researcher used thrust vectoring control to align the thrust direction with the unmanned aircraft's longitudinal axis. A method for controlling a device mechanism using a proportional-integral-derivative (PID) control system. Based on the test results, it has been concluded that the Ziegler–Nichols Method in P controller, the Ziegler–Nichols Method in PD controller, and the Trial-and-Error method in PID controller are the most effective methods for maintaining system stability and achieving the setpoint. It took 0.693, 1.441, and 0.563 seconds respectively to reach the desired value. The researcher used computational fluid dynamics and equations of motion to simulate a UAV's speed. The simulation results of using 25% additional thrust while moving at a 2-degree angle showed that the unmanned aerial vehicle's speed increased by 35.3% compared to the unmanned aerial vehicle without the auxiliary thrust system. When the pitch angle was increased to 5 degrees, the speed of the UAV increased by 15.9%. At higher pitch angles of 10 degrees, the UAV's speed increased by 6.86%. Finally, at pitch angles of 15 degrees, the speed of the UAV increased by 4.97%.
Keywords: Advanced Control Systems Design; Aerospace Engineering and Control Systems; Adaptive Control of Nonlinear Systems